PopSaude (Pop Health): tips for health and wellness on television - a preview note - Cruz, Isabel C.F. da (Online Brazilian Journal of Nursing, 2005)
PopSaude (Pop Health) is a regular television broadcast that is intended to air a finite number of episodes related to health and wellness. The PopSaude content is factual related to women health, African-Brazilian health, physical activities and exercises and health nutrition.